Promote or inhibit: State-owned equity participation and family firms' innovation investment - Kanghong Li; Yuyan Xiang; Changbao Zhou; Lin Runhui (Journal of Innovation & Knowledge (JIK), 2023)
Targeting A-share listed family firms on the Shanghai and Shenzhen Stock Exchange, this study focuses on the special situation of state-owned equity participation in non-state-owned enterprises. Specifically, we explore the relationship between state-owned equity participation, intergenerational succession in family firms, and innovation investments. The results reveal a prominent 'double-edged sword' effect of state-owned equity participation on family firms; that is, there is a reversed U-shaped relationship between shareholding proportion and innovation investment. To some extent, the intergenerational succession of family firms moderates the reversed U-shaped relationship. Moreover, the double-edged sword effect of state-owned equity is more prominent in family businesses that are created by the entrepreneur from scratch. Compared to existing research arguing for the linear relationship between state-owned equity participation and innovation investment by enterprises, we reveal the impact of the excessive supervision effect arising from the increase in state-owned equity holdings on family firms' innovation. This study confirms the double-edged sword effect of state-owned equity participation in family firms and further explores the influence of intergenerational succession and the heterogeneity of family firms on such an effect. By revealing the double-edged sword effect of state-owned equity holdings, this study enriches the research on the participation of private enterprises in mixed-ownership reform.
Keywords: 650; Family firms; Innovation investment; Mixed-ownership reform; State-owned equity; Succession; G32; L22; O32; P31